Inauguración del Edificio B. (UNED, 2024)
Aparece Sergio Flores Álvarez, Carmen María Gutierres Iglesias, Cecilia Dobles, Ileana Piedra Rodríguez, Lucía Herrera Obando, María Auxiliadora Durán, Patricia Rodriguez Peña, Osvaldo Solano Peralta